Dual action antimicrobial surfaces via combined nitric oxide and silver release. Issue 6 (24th September 2014) - Storm, Wesley L.; Johnson, Justin A.; Worley, Brittany V.; Slomberg, Danielle L.; Schoenfisch, Mark H.
Abstract Recent research has demonstrated that silver sulfadiazine and small molecule nitric oxide (NO) donors kill a number of bacterial species synergistically in solution‐based assays. Herein, we report on multilayered silica‐based xerogels that release both NO and silver. Release of each agent was achieved by exposing amine‐modified xerogels to high pressures of NO, and doping silver nitrate (AgNO3) into an alkyl‐silane xerogel. Total achievable releases were 3.5 μmol cm−2 and 1.7 ppm for NO and Ag+, respectively, with release of each agent controlled independent of the other. The NO/Ag+‐releasing coating reduced bacterial adhesion and exhibited greater‐than‐additive killing against both Pseudomonas aeruginosa and Staphylococcus aureus. In contrast, cytotoxicity assays against L929 fibroblasts suggest that the combination does not cause greater‐than‐additive killing to mammalian cells. Such materials may prove useful in the design of biomedical devices prone to infection such as bone and surgical screws. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 1974–1984, 2015.